2006
DOI: 10.1111/j.1567-1364.2006.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering NADH metabolism inSaccharomyces cerevisiae: formate as an electron donor for glycerol production by anaerobic, glucose-limited chemostat cultures

Abstract: Anaerobic Saccharomyces cerevisiae cultures reoxidize the excess NADH formed in biosynthesis via glycerol production. This study investigates whether cometabolism of formate, a well-known NADH-generating substrate in aerobic cultures, can increase glycerol production in anaerobic S. cerevisiae cultures. In anaerobic, glucose-limited chemostat sultures (D=0.10 h(-1)) with molar formate-to-glucose ratios of 0 to 0.5, only a small fraction of the formate added to the cultures was consumed. To investigate whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 48 publications
(94 reference statements)
3
29
0
Order By: Relevance
“…Firstly, the high rates of NAD ϩ -dependent formate oxidation may have led to an increased intracellular NADH concentration, which, in turn, may have affected NAD ϩ -dependent reactions delivering precursors for the synthesis of penicillin G. Indeed, it has been reported that glycolysis in microorganisms may be inhibited by the addition of formate via an effect of the FDH reaction on the NADH/ NAD ϩ ratio (6,7,19,34). Secondly, it has been found that the affinity of Saccharomyces cerevisiae FDH for formate is negatively affected by high NADH/NAD ϩ ratios, showing that FDH from S. cerevisiae obeys sequential bi-bi two-substrate kinetics (12,30,37). If the same holds for P. chrysogenum, this kinetic mechanism may have contributed to the rapid increase of the residual formate concentration at high formate-to-glucose ratios, which may have caused further toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the high rates of NAD ϩ -dependent formate oxidation may have led to an increased intracellular NADH concentration, which, in turn, may have affected NAD ϩ -dependent reactions delivering precursors for the synthesis of penicillin G. Indeed, it has been reported that glycolysis in microorganisms may be inhibited by the addition of formate via an effect of the FDH reaction on the NADH/ NAD ϩ ratio (6,7,19,34). Secondly, it has been found that the affinity of Saccharomyces cerevisiae FDH for formate is negatively affected by high NADH/NAD ϩ ratios, showing that FDH from S. cerevisiae obeys sequential bi-bi two-substrate kinetics (12,30,37). If the same holds for P. chrysogenum, this kinetic mechanism may have contributed to the rapid increase of the residual formate concentration at high formate-to-glucose ratios, which may have caused further toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results are likely to be a combination of effects from alleviating the feedback inhibition of the TCA cycle by mitochondrial NADH and increasing respiratory capacity due to improved efficiency of oxidative phosphorylation, as quantified by the P/O ratio (15). There are no reports that describe the effect of increasing NADH in S. cerevisiae, although formate has been used previously as a source of additional reducing power in S. cerevisiae (2,4,11,23,24,27). Formate (HCOO Ϫ ) is efficiently oxidized to CO 2 by NAD ϩ -dependent formate dehydrogenase (27) and, therefore, cannot be used as a carbon source for biomass synthesis.…”
mentioning
confidence: 91%
“…The working volume was kept at 1 liter by a Masterflex peristaltic effluent pump (Barrington, IL) coupled to an electric level sensor. The pH was kept at 5.0 by using an Applikon ADI 1030 biocontroller via the automatic addition of 2.0 M potassium hydroxide (15). Cultures were sparged with air at a flow rate of 0.5 liter min Ϫ1 using a Brooks model 5876 mass flow controller.…”
Section: Methodsmentioning
confidence: 99%
“…Biomass dry mass determination, substrate and metabolite analyses, off-gas analysis, preparation of cell extract, and determination of chemostat culture protein samples were performed as described previously (15). Formate concentrations were confirmed by a colorimetric method (24).…”
Section: Vol 74 2008 Engineered S Cerevisiae Coconsuming Formaldehmentioning
confidence: 99%